PENGELOLAAN DAN PENERIMAAN SOSIAL AGROFORESTRI TRADISIONAL DUKUH DI KABUPATEN BANJAR KALIMANTAN SELATAN - Hafizianor Hafizianor; Herry Iswahyudi (Universitas Lambung Mangkurat, 2016)
Banjar District, one of which district that most peoples working as farmer in between gardening fruit, and present the results from the orchard began to decline. The purpose of this study is: (1) The Management of traditional agroforestry dukuh in The Banjar District (2) Knowing the social acceptance of the existence of an orchard with traditional agroforestry dukuh in the district of Banjar (3) Knowing the factors that influence the social acceptance of the existence of the orchard. Obtain data used 2 methods primer and secondary data. Population of this study used purposive sampling. As for knowing the factors that influence people's social acceptance of the existence of an orchard used Multiple Linear Regression Analysis, processed through Statistical Program for Social Sciences. Obtained by calculating an index score of each elements of the social acceptance of such participation, attitudes and values, it is mean peoples still have high levels of social acceptance the orchard. The results showed the traditional management system of dukuh consist of the local community wisdom value . The contribution that given by the traditional agroforestry dukuh from the economic sector is siginificant enough amount of 33% of the community income totally in a year so that the performance of traditional agroforestry is good for the side of productivity, sustainability, justice and eficiency showing the good condition. Level social acceptance of existence the orchard with traditional agroforestry dukuh, according to the analysis of data obtained has high acceptance rate, is 82.86. As for factors that affected, the results of multiple linear regression analysis of testing is known that the seven factors affected social acceptance, there are three factors that significantly influence social acceptance, namely income, production, and marketing.